Signifikansi perbedaan produktivitas, omzet dan pemanfaatan digital marketing pada anggota Ikatan Wanita Pengusaha di Daerah Istimewa Yogyakarta, sebelum dan saat pandemi Covid 19 - Indah Kurniawati; Beni Suhendra (Formosa Journal of Multidisciplinary Research, 2022)
The Covid 19 pandemic that plagued the world caused the paralysis of the world economy. In Indonesia, not only MSMEs are affected, but large companies are also affected by the Covid 19 pandemic. The purpose of this study was to analyze and test the differences in the significance of productivity, turnover and utilization of digital marketing in members of the Indonesian Women Entrepreneurs Association of Yogyakarta Special Region (IWAPI DIY) before and during the Covid 19 pandemic. The study used primary data. Testing uses the one sample normality test Kolmogorof Smirnor and other tests using the Wilcoxon Signed Rank Test.The results showed that the productivity and business turnover of IWAPI DIY members differed significantly between before and after the Covid 19 pandemic. The results of the digital marketing test showed no significant difference between before and after the Covid 19 pandemic.While the results of digital marketing utilization testing showed there was no significant difference between before and after the Covid 19 pandemic.This shows that before the Covid 19 pandemic, businesses, especially IWAPI DIY members, had done business marketing using digital marketing, especially via sosmed, namely Whatshapp, Instagram, Facebook or through marketplaces such as Shopee, Bukalapak, Gojek, Grab and others